Penile Artery Shunt Syndrome: A Novel Cause of Erectile Dysfunction after Penile Revascularization Surgery. (10th April 2014) - Pavlinec, Jonathan G.; Hakky, Tariq S.; Yang, Christopher; Massis, Kamal; Munarriz, Ricardo; Carrion, Rafael E.
Abstract Introduction Penile revascularization is a surgical treatment option for erectile dysfunction (ED) in healthy individuals due to a focal arterial occlusion in the absence of generalized vascular disease. Most described failures have been attributed to graft stenosis or disruption of the anastomosis. Aim We report a novel phenomenon called Penile Artery Shunt Syndrome that contributed to persistent ED in a patient after penile microvascular arterial bypass surgery. Methods A 26‐year‐old man presented for evaluation of long‐standing ED, which was attributed to trauma sustained 12 years earlier. He had difficulty obtaining and maintaining erections despite oral pharmacotherapy. Clinical data related to the case were studied, analyzed, and reviewed with urologic and radiologic specialists at multiple centers that collaborated in the care of this patient. Main Outcome Measures Penile duplex ultrasound peak systolic velocities and five‐item International Index for Erectile Function questionnaire scores were the main outcome measures. Results Initial diagnostic workup of the patient confirmed severe insufficiency of the left cavernosal artery, with no evidence of venous leak. The patient underwent penile microvascular arterial bypass surgery with anastomosis of the left inferior epigastric artery to the left dorsal penile artery. The patient had persistence of severe ED despite patent anastomosis by penile duplex ultrasound. Subsequent arteriography revealed an arterial shunt due to an aberrant obturator artery arising from the donor inferior epigastric artery. The patient underwent embolization of the aberrant obturator artery, with resolution of the shunt and marked improvement in erectile function. Conclusions The presence of an aberrant obturator artery arising from the inferior epigastric artery may predispose to persistent ED after revascularization due to the creation of a shunt phenomenon. Pelvic arteriography may be useful in identifying anomalous anatomic considerations prior to penile revascularization and to evaluate patients with persistent postoperative ED. Pavlinec JG, Hakky TS, Yang C, Massis K, Munarriz R, and Carrion RE. Penile Artery Shunt Syndrome: A novel cause of erectile dysfunction after penile revascularization surgery. J Sex Med 2014;11:2338‐2341.